PROtective ileoStomy versus ProtectivE colostomy in anterior Rectal resectIon: study protocol for a multicenter, open-label, randomised conTrolled studY (PROSPERITY) - Ville Sallinen; Reetta Satokari; Toni Seppälä; Panu Mentula; Laura Koskenvuo; Pirita Varpe; Carola Haapamäki; Anna Lepistö; Paavo Paajanen; Monika Carpelan-Holmström; Anu Carpelan; Kirsi Lehto (BMJ Open)
Introduction Loop ileostomy and loop colostomy are both used to form a protective stoma after anterior resection. Evidence regarding which of these two procedures is superior is lacking. Furthermore, no studies comparing changes in the microbiome after loop ileostomy or loop colostomy exist.Methods and analysis This multicentre, open-label, superiority, individually randomised controlled trial will include patients who undergo anterior rectal resection with primary anastomosis with a protective stoma. The exclusion criteria are patients who already have a stoma, technical inability to create either type of stoma, aged <18 years and inadequate cooperation. Patients scheduled for anterior rectal resection will be randomised intraoperatively in a 1:1 ratio to undergo either loop ileostomy or loop colostomy. The primary outcome is cumulative stoma-related adverse events within 60 days after primary surgery, measured using the Comprehensive Complication Index (CCI). Secondary outcomes include all postoperative complications (measured using the CCI), number of hospital-free days within 30 days after primary surgery, quality of life at 2 months (measured using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaires-Core 30 and Colorectal 29), complications within 30 days after stoma closure (measured using the CCI) and kidney function (measured using estimated glomerular filtration rate) at 1 year. Tertiary outcomes are survival, kidney function and number of stoma site hernias at 5 years. The sample size was calculated to detect a mean difference of five CCI points between groups, resulting in a final sample size of 350 patients. Microbiome samples will be collected from the faeces and mucous membrane from patients in Helsinki University Hospital.Ethics and dissemination The Ethics Committee of Helsinki University Hospital approved the study (approval number 4579/2024). The findings will be disseminated in peer-reviewed academic journals.Trial registration ClinicalTrials.gov, NCT06650085, registered on 20 August 2024. Protocol version: Version 3.0, dated 17 April 2025.